2020
DOI: 10.1093/inthealth/ihaa031
|View full text |Cite
|
Sign up to set email alerts
|

Household motor vehicle ownership and obesity among Indian females and males: 2005–2016

Abstract: Background To determine associations between household motor vehicle ownership and obesity among Indian adults. Methods Bivariate and multivariable analyses were conducted using the 2005–2006 and 2015–2016 Indian Demographic and Health surveys, with over 800 000 respondents. Results Obesity prevalence (body mass index ≥25 kg/m2) rose in females (16.87% to 20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Similarly, a study set in China found that the association between neighbourhood characteristics and individual risk of being overweight among middle-aged and older adults was mediated by the odds of owning a car and spending less time being physically active ( Wang, Feng, et al, 2019 ). Still in the Asian context, a study based in India found that motor vehicle ownership was significantly associated with obesity, particularly for women ( Kellstedt et al, 2021 ), while a study set on rural China found that increases in population density were associated with weight gain through increasing car ownership ( Yin et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, a study set in China found that the association between neighbourhood characteristics and individual risk of being overweight among middle-aged and older adults was mediated by the odds of owning a car and spending less time being physically active ( Wang, Feng, et al, 2019 ). Still in the Asian context, a study based in India found that motor vehicle ownership was significantly associated with obesity, particularly for women ( Kellstedt et al, 2021 ), while a study set on rural China found that increases in population density were associated with weight gain through increasing car ownership ( Yin et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%